Attacks of Denial-of-Service on Networks Layer of OSI Model and Maintaining of Security - Azeem Mohammed Abdul; Syed Umar (Institute of Advanced Engineering and Science, 2017)
The emergence of wireless sensor networks as one of the technology trends in the coming years, and some special tests of safety. The event will be thousands of tiny sensors that cheap devices, memory, radio and make, in most cases, no access to the production and energy. Some great challenges of sensor networks are different; we focus on security in the form of wireless sensor networks. To some network wireless sensor network in order to optimize use of the sensor, so that the network can be as long as possible. But the management of the important mission of the sensor network, denial of service (DoS) attacks against the destruction of the efficient use of network resources and the vital functions of the network. DoS attacks can be one of the greatest threats to security threats be considered. In fact, there are many different layers of the OSI-DOS.